Synthesis of Polyfunctionalised 2-Piperidinones Catalysed by Fe(acac)3 - Talbot, Eric P. A. (Synlett, 2019)
Herein is reported the synthesis of polyfunctionalised piperidines and 2-piperidinones, through hydrogen atom transfer (HAT) chemistry catalysed by Fe(acac)3. The nature and substitution around the Michael acceptor, as well as the allylic amine, allowed access to all positions of the piperidine ring. The chemistry tolerates a range of different functionalities, allowing the investigation of new and diverse scaffolds.
Keywords: HAT; piperidinone; Michael addition; piperidines; iron; radicals